2022
DOI: 10.1021/acs.jpcc.1c10635
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Factors Affecting the Mechanical Properties of Halide Perovskites from First-Principles Calculations

Abstract: In practical applications, the mechanical properties of halide perovskites (e.g., ABX3; A = monovalent cation; B = divalent metal cation; X = halogen anion) are of fundamental importance in achieving the durability of perovskite-based devices. In contrast to the widely studied photovoltaic properties, the composition/structure–mechanical property relationship in halide perovskites remains largely unexplored. Here, taking cesium-based halide perovskite models as examples, we have investigated the effects of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…It has a crucial impact on the mechanical properties of halide perovskites when some factors such as phase transition and structural dimensionality are taken into account. 71…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a crucial impact on the mechanical properties of halide perovskites when some factors such as phase transition and structural dimensionality are taken into account. 71…”
Section: Resultsmentioning
confidence: 99%
“…It has a crucial impact on the mechanical properties of halide perovskites when some factors such as phase transition and structural dimensionality are taken into account. 71 More mechanical parameters including the bulk modulus (B), shear modulus (G), Young's modulus (Y), and Poisson's ratio (n) can be gained through the Voigt-Reuss-Hill (VRH) approximation in the literature. [72][73][74] The values of B, G, and Y slightly decreased from AZrS 3 to AZrSe then this solid is brittle, otherwise, it is ductile.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…The accurate description of their electronic properties demands the inclusion of spin-orbit coupling [32][33][34]. Moreover, the complex structure of these materials combined with the peculiar softness of their lattices requires non-standard methods [35][36][37][38][39]: for example, it was recently demonstrated that the lattice contribution to the screened Coulomb interaction should be explicitly incorporated in order to obtain accurate estimates of the exciton binding energies [40].…”
Section: Introductionmentioning
confidence: 99%
“…The relation between C 11 in different phases is C > O > T, which is different from C > T > O in the first-principles calculation. 22,23 Anisotropy of Young's Modulus and Poisson's Ratio. To investigate the directional dependence of elastic properties, we use the ELATools program 42 to analyze the directional dependence of Young's modulus and Poisson's ratio for each phase of CsPbI 3 with respect to different crystallographic directions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%